PARTIAL DIALLEL ANALYSIS OF MAIZE INBRID LINES FOR KERNAL YIELD AND ITS COMPONENTS IN SULAIMANI-IRAQ - sheikh Abdulla, S. M.; Abdulkhaliq, D. A.; I. Towfiq, Sh. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to investigate combining ability among maize inbred lines. Randomized complete block design with three replicates was used to study the general combining ability of parents, and specific combining ability of 12 F1s. Combining ability was studied in a partial diallel cross in maize for traits yield and attribute at two locations (Qlyasan and Kanipanka) at Sulaimani Governorate. The cross 3×6 produced the highest value kernels yield and most of the attributed traits as the average of both locations. Mean squares due to crosses, GCA and SCA were highly significant for most traits as the average of both locations. The ratio of σ2gca/ σ2sca was found to be less than one for all traits except days to silking and rows/ ear at the first location, ears/plant, and kernels/row at the second location, and days to silking, plant height, rows/ear and kernels/row as the average of both locations which were more than one, this confirms the importance of both additive and non-additive gene effect in the inheritance of these traits. Heritability in broad-sense was found to be highest for days to tasseling and silking, ear width, kernels/row, and 300 kernels weight, while for narrow sense, it was low to moderate for different traits.